Working Algorithms: Software Automation and the Future of Work. (November 2017) - Shestakofsky, Benjamin
While some argue that the rise of software automation threatens workers with obsolescence, others assert that new complementarities between humans and software systems are likely to emerge. This study draws on 19 months of participant-observation research at a software firm to investigate how relations between workers and technology evolved over three phases of the company's development. The author finds two forms of human–software complementarity: computational labor that supports or stands in for software algorithms and emotional labor aimed at helping users adapt to software systems. Instead of perfecting software algorithms that would progressively push people out of the production process, managers continually reconfigured assemblages of software and human helpers, developing new forms of organization with a dynamic relation to technology. The findings suggest how the dynamism of the organizations in which software algorithms are produced and implemented will contribute to labor's enduring relevance in the digital age.